The Impact of Independent Curriculum Training on the Teaching Skills of Elementary School Teachers - Dwi Pudiyati; Sri Marmoah; Supianto (Jurnal Ilmiah Sekolah Dasar, 2025)
This research is motivated by the importance of improving teachers' teaching skills in line with the implementation of the Independent Curriculum, which demands more adaptive and student-centered learning. This study aims to analyze the impact of the Independent Curriculum training on improving the teaching skills of elementary school teachers. This study uses a qualitative, descriptive approach to explore in-depth changes in teacher competency after participating in the training. The research subjects consisted of the principal and several teachers directly involved in the training. Data were collected through observation, interviews, questionnaires, and documentation techniques, using observation guidelines, interview guides, questionnaires, and documentation as research instruments. The data obtained were analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results show that the Independent Curriculum training can improve teachers' skills in designing and implementing differentiated learning, applying flexible learning strategies, and managing classes more effectively. The conclusions of this study confirm that the training makes a positive contribution to teacher professionalism. The implications of this study indicate the need to strengthen ongoing training programs to support improvements in the quality of learning that is more responsive to student needs.